Medicinal potential of gambier extract for recurrent aphthous stomatitis treatment - Amaliah, Nurfitri; Saud, Muhammad Yamin (Jurnal Prima Medika Sains, 2025)
Recurrent aphthous stomatitis (RAS) remains as one of the most common disorders in the oral cavity. Various treatment options for RAS conditions include topical, systemic, and the use of traditional ingredients that have pharmacological content. One of the plants known to have good pharmacological content for RAS treatment is gambier (Uncaria Gambier). Gambir plant extract is known to have various benefits for health, including in the management of RAS due to the active ingredient compounds in the form of anti-inflammatory, antioxidant and antibacterial properties. One of the active compounds possessed by gambier plant extract in the form of catechine is proven to have the ability to reduce inflammation and help to accelerate the healing process in RAS cases.